Rapid Identification of Improved Protein Ligands Using Peptoid Microarrays - Lim, Hyun-Suk (Bioorg Med Chem Lett, 2009)
A rapid array-based protocol is presented by which a modest affinity protein-binding small molecule can be appended to a library of peptoids via Click chemistry. The array can then be screened for improved ligands that exhibit a higher affinity for the protein target.